Public transport management systems with real-time passenger information - Nunes, Catarina Alexandra do Espirito Santo (2022)
Public transport information systems play a key role in the usage of transport services by providing information and tools so that users can navigate complex transport networks. Included in those systems are often applications that explore topics such as accessibility, transport occupancy and journey planning. Developments in the area have been made thanks to the collaboration between public agencies and the open-source community through the usage and availability of real-time transport data. Here we evaluate the available solutions, the underlining problems in the public transport space and build a solution for a public transport mobile application for the city of Évora, Portugal; Sumário: Sistemas de informação para transporte público com informações para passageiros em tempo real - Sistemas de informação para transportes públicos têm um papel-chave no uso de transportes públicos, ao fornecer informação e ferramenta que permitem aos utilizadores navegar redes de transporte complexas. Nesses sistemas é comum a exploração de temas como a acessibilidade, ocupação de transportes e planeamento de viagens. Os desenvolvimentos recentes na área foram realizados graças à colaboração de agências públicas com a comunidade de desenvolvimento de código aberto através do uso e viabilidade de dados de transporte em tempo real. Aqui as soluções disponíveis no mercado e os problemas subjacentes ao espaço dos transportes publico são avaliados, e uma solução para uma aplicação para os transportes públicos de Évora, Portugal, é desenhada e desenvolvida.